18.1k views
4 votes
Use the “complete the square” method to solve the following problemx^2 + 3x + 11 = 0

User Sam Manzer
by
4.7k points

1 Answer

3 votes


x^2+3x+11=0
((1)/(2)*3)^2=(+(3)/(2))^2
\begin{gathered} x^2+3x=-11 \\ x^2+3x+(+(3)/(2))^2=-11+(9)/(4) \\ \\ (x+(3)/(2))^2=-(35)/(4) \\ \\ x+(3)/(2)=\sqrt{(-35)/(4)} \\ \\ x+(3)/(2)=\pm(√(35))/(2)i \\ \\ x=(-3)/(2)\pm(√(35))/(2)i \end{gathered}

The answers are


x=(-3)/(2)+(i√(35))/(2),\text{ }x=(-3)/(2)-(i√(35))/(2)

User ElKePoN
by
4.2k points